2021
DOI: 10.3390/molecules26113383
|View full text |Cite
|
Sign up to set email alerts
|

A New Chalcone Derivative with Promising Antiproliferative and Anti-Invasion Activities in Glioblastoma Cells

Abstract: Glioblastoma (GBM) is the most common and most deadly primary malignant brain tumor. Current therapies are not effective, the average survival of GBM patients after diagnosis being limited to few months. Therefore, the discovery of new treatments for this highly aggressive brain cancer is urgently needed. Chalcones are synthetic and naturally occurring compounds that have been widely investigated as anticancer agents. In this work, three chalcone derivatives were tested regarding their inhibitory activity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…In this study, we found that Chalcone 9X showed a lower cytotoxic effect than Chalcones 1 for human normal cell lines, and the security is much better than Chalcones 1. 100 μ mol/L Chalcone 9X had little cytotoxicity to normal astrocyte HA1800 cells, while 100 μ mol/L Chalcone 1 showed very high cytotoxicity to nontumor cell line [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, we found that Chalcone 9X showed a lower cytotoxic effect than Chalcones 1 for human normal cell lines, and the security is much better than Chalcones 1. 100 μ mol/L Chalcone 9X had little cytotoxicity to normal astrocyte HA1800 cells, while 100 μ mol/L Chalcone 1 showed very high cytotoxicity to nontumor cell line [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chalcones have been demonstrated to inhibit tumor progression and development in cancers [12][13][14][15][16][17][18], including glioma [15,18]. The synthetic Chalcone 9X is an aromatic ketone, which has been proved to own antitumor activities in lung cancer cells and hepatic cancer cells through activating Caspase-3 and Caspase-8 signaling pathway [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The scaffold associated to flavonoids is very versatile and has long been recognized for the wide range of pharmacological activities, such as anti-inflammatory, cardioprotective, antimicrobial, anticancer, and neuroprotective [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. The interest in these compounds in Medicinal Chemistry is evidenced by the fact that several flavonoids have been marketed or clinically tested for various health conditions.…”
Section: Introductionmentioning
confidence: 99%